2016
DOI: 10.1016/j.idairyj.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dairy phospholipid preparative extraction protocols in combination with analysis by high performance liquid chromatography coupled to a charged aerosol detector

Abstract: a b s t r a c tDifferent fat extraction methodologies, R€ ose Gottlieb (RG), Folch with CaCl 2 (F1) and Folch without CaCl 2 (F2) were evaluated alongside a high performance liquid chromatography (HPLC)-based analytical protocol involving a charged aerosol detector (CAD) to optimise the separation and quantification of dairy phospholipids (PLs). Total PL recovery by F2 proved to be 1.8-and 2.5-fold greater than RG and F1, respectively. Alteration of the HPLC elution program maximised peak separation and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Whole milk contains about twice the PLs of skim milk, while some dairy co-products can become relatively enriched in PLs, including buttermilk and butter serum [29]. Phospholipid content in whole milk can vary between 0.7 to 2.3 g/100 g of fat [30][31][32][33][34]. This variation in the level of reported PL content in milk can be attributed to the different analytical techniques used, as well as the diet [35], season of the year [36], age, and stage of lactation of the animal [37,38].…”
Section: Milk Polar Lipids: Classes and Quantitymentioning
confidence: 99%
See 3 more Smart Citations
“…Whole milk contains about twice the PLs of skim milk, while some dairy co-products can become relatively enriched in PLs, including buttermilk and butter serum [29]. Phospholipid content in whole milk can vary between 0.7 to 2.3 g/100 g of fat [30][31][32][33][34]. This variation in the level of reported PL content in milk can be attributed to the different analytical techniques used, as well as the diet [35], season of the year [36], age, and stage of lactation of the animal [37,38].…”
Section: Milk Polar Lipids: Classes and Quantitymentioning
confidence: 99%
“…Cream is rich in fat (~32%) and protein (~2%) [31] and has 0.3-5.65 g of PL/100 g of fat. Most authors reported PE being the most abundant PL found in cream, followed by PC and SM [30,32,42,43]. Butter (~78% fat) [32] has a PL content ranging from 0.195-5.31 g/100 g fat.…”
Section: Milk Polar Lipids: Classes and Quantitymentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison of all these procedures suggest a solvent‐associated effect for less abundant compounds (e.g. phosphatidylinositol or ceramides) that may also be related to slight inter‐laboratory variations from the original method . However, in the last years some studies reported these solvent modifications involving MTBE or butanol as reliable procedures .…”
Section: The Complexity Of Lipid Isolationmentioning
confidence: 99%